A NEW SPECIES OF GENUS AGROTIS OCHSENHEIMER (LEPIDOPTERA: NOCTUIDAE) IN PAKISTAN - M. Sajjad; Z. M. Sarwar¬; M. Binyameen; M. Qasim; M. H. Bashir (Journal of Animal and Plant Sciences, 2020)
The family Noctuidae has most important insect pests which damage the cereal and cash crops. For proper identification and classification of these insect pests, taxonomy plays a vital role form successful management strategy. In the present study, several diagnostic characteristics were examined but typically concentration was made on genitalia for the proper identification of species. Specimens were dissected carefully and genitalia were examined under Stereo microscope. As a result, Agrotis hirsutumus is new to science and the first time described from Pakistan. Agrotis species which have been reported from Pakistan are also included in the key.
Keywords: Agrotis: hirsutumu; Bahawalpur; Male Genitalia; Systematic Study; Pakistan